Molecular Phylogenetics and Molecular Dating of Arecaceae In Bangladesh Inferred from Matk and Rbcl Genes (Bangladesh Journal of Plant Taxonomy, 2023)
A molecular phylogenetic investigation was undertaken for 30 species belonging to 15 genera of the palm family Arecaceae in Bangladesh to infer evolutionary relationships and molecular dating utilizing plastid-based matK and rbcL genes through multifaceted-algorithm driven approaches with Neighbor-Joining, Maximum-Likelihood, and Bayesian Inference methods. The study revealed that matK has better species discrimination efficiency than rbcL gene due to its highly variable nature. Transition/transversion bias test corroborated this finding as matK showed higher bias (2.632) than rbcL (2.235). Nucleotide substitution patterns were visualized via HYPERMUT program, which unveiled higher variability in matK and lower variability in rbcL alignment. Phylogenetic trees constructed with matK revealed monophyletic nature of origin for all the three subfamilies, viz. Arecoideae, Coryphoideae and Calamoideae, while rbcL trees exhibited polyphyly for Coryphoideae and monophyly for Arecoideae and Calamoideae. All the nine tribes belonging to three subfamilies demonstrated monophyletic nature in matK trees. Bootstrap support and Bayesian posterior probability were found to be higher in matK topologies than that of rbcL. The molecular clock test unraveled an equal evolutionary rate for matK and unequal rate for rbcL sequences. Molecular dating approach unveiled Calamoideae to be the most ancient subfamily (65.75 MYA) among the three subfamilies that originated during the Late Cretaceous period in the Mesozoic era, whereas Coryphoideae and Arecoideae were found to have originated in the Cenozoic era.Bangladesh J. Plant Taxon. 30(2): 213-232, 2023 (December)